Digital Image Analysis Of Cracks In Concrete - Abdul Rahman, Hasliza (Universiti Sains Malaysia, 2005)
The image analysis technique for the automatic detection and quantification of cracks in concrete is described. The presence of cracks can significantly influence the mechanical and mass transport properties of concrete. Over the past 20 years, several techniques have been developed to detect and measure micro-cracks in concrete. This image analysis technique allows the assessment of the characteristics of the crack network in concrete. The technique of the image analysis is essentially a three-step process that includes the preparation of the samples, segmentation of the cracks, and the treatment of the collected data. The first procedure carried out in this study was the preparation of the concrete samples of the three different characteristics strength. The compressive strength of the samples was taken on 7 and 28 days. Image of cracks on the concrete samples were taken using digital camera and were analyzed using IDRISI sofware. The segmentation includes a treatment of the color image, thresholding on the gray level histogram and treatment of the binary images. The resulting images are then treated and finally the characteristic of the cracking pattern are determined.